PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN EDPUZZLE KEPADA SISWA KELAS IV GUGUS V KECAMATAN GEROKGAK - Made Dendi Aditya Putra; I Made Sedana; IG Agung Jaya Suryawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop interactive multimedia assisted by Edpuzzle for fourth-grade elementary school students in the IPAS subject on the topic "Daerahku Kaya Sumber Daya", as well as to determine its validity and practicality. This research employed a Research and Development (R&D) approach using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects involved material experts, media experts, language experts, teachers, and fourth-grade students. Data were collected through interviews, observations, documentation, and questionnaires. The data were analyzed using descriptive qualitative and quantitative techniques. The results showed that the developed multimedia achieved a very high level of validity. The material expert validation score reached 0.98, media expert validation reached 0.93, and language expert validation reached 0.98. Furthermore, the practicality test results showed a score of 92% from teachers and 92.84% from students, both categorized as very practical. Therefore, the Edpuzzle-assisted interactive multimedia is considered valid and highly practical for use in elementary school IPAS learning.